Analysis of Grammatical Cohesion Errors in Explanatory Texts 11th Grade Students of SMA Santo Petrus Medan - Sihite, Jernyta; Simanjuntak, Dairi Sapta Rindu; Gultom , Candra Ronitua; Ginting, Angelina Pascalia (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe the grammatical errors found in explanatory texts written by eleventh-grade students of SMA Santo Petrus Medan in the 2024/2025 academic year. The research was conducted during the even semester, from January to June 2025. The population included all eleventh-grade students, with a sample of 90 texts selected from class XI using purposive sampling. Data collection instruments included written tests, documentation, and observation. The data analysis technique employed the distributional method (metode agih) by Sudaryanto, utilizing the basic technique of Immediate Constituent Analysis (BUL) along with advanced techniques such as deletion and substitution. The results show that the most dominant grammatical errors were found in the use of grammatical cohesion, particularly in reference and conjunction. Reference errors include unclear or contextually inappropriate pronouns, while conjunction errors include excessive use, improper choice, or absence of necessary connectors. Data were presented systematically with coded references to clearly identify each error and its context. These findings highlight the need for writing instruction that emphasizes discourse structure and grammatical cohesion to help students produce more coherent and effective texts.